Old townscapes of China - Liu, Bin; Sun, Lei; Yu, Qiu; Li, Lei (Beijing, China : Foreign Languages Press, 2008)
When bulldozers nudge their way toward the increasingly fewer Beijing hutong and siheyuan, and Shanghai linong, it is not only the old city districts that are declining; the Chinese architecture, culture and lifestyle are vanishing with them.
Keywords: Cities and towns, Ancient -- China; China -- Guidebooks; China -- Description and travel